The level of oral proficiency reached by the students attending advanced english II courses, during semester I of the year 2003 - Lovato Hernández, Zoila Edith (Universidad de El Salvador, 2003)
In the following pages, it is presented the essay which contains all the information that is related to the level of oral proficiency reached by the students that were attending classes at Advanced Intensive English II courses during the first semester of the year 2003. In the present days, most of the people who study English as a second language do it because they want to have the capacity to communicate their ideas, thoughts and feelings not only in a written way, but also in an oral way. However, not all the people have the capacity to obtain specific levels of oral proficiency; that is what happens to many language students that attend classes at the University of El Salvador. This is due to a series of facts that take place during the whole English learning process, and they are described through the development of this work. Being their major interest to become proficient in a second language, students place the speaking ability as one of their main goals of study. Then in order to fulfill the needs of the students, the teachers must base their teaching on those communicative activities that best will fit on the development of adequate levels of accuracy when practicing the language. It is for that reason that this essay makes emphasis on the use of some principles stated in the form of hypothesis that can help teachers when planning instruction. Those principles were created by Alice Omaggio, and they are described carefully in the theoretical framework presented in this essay. Besides, are mentioned some of the principles that can be used by teachers are mentioned in order to select the best techniques and strategies that can help to improve students´ second language oral proficiency. Since in the learning of English, the ones that receive most benefits are the students, then they are the ones that have to do the most part of the work if they really want to succeed in the learning of English. They have to look for those strategies and techniques that can help them to increase their proficiency. In this essay are explained some of the strategies and techniques that can be used by teachers and students to develop levels of proficiency. Students should bear in mind that the more they practice the language, the more they will develop their speaking skill, and in that way achieve the required levels of proficiency.